WHY SINGLES PREFER TO RETIRE LATER: THE ROLE OF RETIREMENT ANXIETY AND SPOUSAL PULL - Eismann, M (Innov Aging, 2018)
Due to increasing divorce rates and lifelong singlehood, a growing number of older workers approach retirement age as singles. Previous research has shown that singles intent to and actually do retire later than their partnered counterparts, but we know little about why the retirement transitions of single and partnered older workers differ from one another. We add to a literature that is dominated by financial arguments and hypothesize that retirement anxiety and spousal pull (due to preferences for joint leisure) contribute to the difference in retirement preferences by relationship status. To test our hypotheses, we analyzed data from the NIDI Pension Panel Survey (2015), a study of about 6,800 older workers (age 60–65) in the Netherlands. We used ordinal logistic regression and the KHB method to investigate mediation effects and we controlled for important socio-demographic and economic variables in all our analyses. The results lent support to our hypotheses, particularly for men. Differences between male single and partnered workers were fully explained by retirement anxiety about the consequences of retirement for social contacts and time structure and by spousal pull. For women, the hypothesized explanations were also at work, but they could not fully explain why singles preferred to retire later. Our findings suggest that the retirement transition has a different meaning for older workers who are single as compared to partnered. Moreover, singlehood seems to shape the retirement transition of men and women differently.